Priorities and Future Actions for an Effective Use of Phytotherapy in Livestock—Outputs from an Expert Workshop - Blanco-Penedo, Isabel; Fernández González, César; Tamminen, Lena-Mari; Sundrum, Albert; Emanuelson, Ulf (Frontiers in Veterinary Science, 2018)
This study reflects on the recognised need for more joined-up, high-quality research on phytotherapy that addresses the current societal challenges in finding alternatives to the use of antibiotics. The study applied a multidisciplinary participatory approach in an expert workshop exercise within the FP7 EU IMPRO project. Prior to this study, a literature review was elaborated on research in the field of phytotherapy as applied to farm animals, cooperation between research bodies and initiatives to reduce the use of antibiotics by using phytotherapeutic remedies. The review was delivered to the participants of the workshop so as to receive feedback on it and enrich the discussion. Different expertise, background in research or veterinary practice, and varying positions regarding phytotherapy were the criteria in targeting participants. A structured workshop was subsequently organized, with questions to experts addressing scientific validation of phytotherapy, effective treatment under farm conditions and necessary developments for the future. Challenges identified by the experts were: poor study designs, lack of reproducibility of studies, poor standardization of products, cost-benefit concerns, lack of veterinarian training and poor data availability. To overcome obstacles, the need for improved study designs for clinical trials was given priority in order to prove the efficacy of remedies and to implement a monitoring system which enables the assessment of the effectiveness of treatments in farm practice. Reflections in this report are intended to be a resource for scientists, policy makers and end users for an effective use of phytotherapy at farm level.